Answer:
The answer in the procedure
Step-by-step explanation:
we have
2x-3y=-1 ----> equation A
3x+3y=26 --> equation B
Solve the system by elimination
Adds equation A and equation B
2x-3y=-1
3x+3y=26
----------------
2x+3x=-1+26
5x=25
x=25/5
x=5
Find the value of y
substitute the value of x in equation A or equation B and solve for y
2(5)-3y=-1
10-3y=-1
3y=10+1
y=11/3
Answer:
x = 9
y = 9√3 = 15.6
Step-by-step explanation:
The triangle given is a right triangle, therefore:
✔️apply trigonometric ratio formula to find x:
Reference angle = 60°
Hypotenuse = 18
Adjacent = x
Thus:
Cos (60) = x/18
Multiply both sides by 18
18×cos(60) = x
9 = x
x = 9
✔️find y by applying pythagorean theorem:
y² = 18² - x² (pythagorean theorem)
y² = 18² - 9² (substitution)
y² = 243
y = √243
y = √(81*3)
y = 9√3 = 15.6
Answer:
-1/2
Step-by-step explanation:
This is a negative slope so therefore the final answer is negative. You can use rise over run since a graph is provided. Start from point (0,3) count down until you get to the line if the second point. That would be 2 down...then you count across to the point. That's 4. The slope is -2/4 but simplified is -1/2.
Answer:
0,252
Step-by-step explanation:
De la pregunta,
1 minuto = 0.08
3,15 minutos = x
Cruz multiplicar
x = 3,15 × 0,08
x = 0,252
Por tanto, por su última llamada que duró 3,15 minutos, Laura estaría pagando 0,252